What Leads to Lead: Results of a Nationwide Survey Exploring Attitudes and Practices of Orthopaedic Surgery Residents Regarding Radiation Safety. (7th February 2018) - Bowman, James R.; Razi, Afshin; Watson, Shawna L.; Pearson, Jeffrey M.; Hudson, Parke W.; Patt, Joshua C.; Ames, S. Elizabeth; Leddy, Lee R.; Khoury, Joseph G.; Tubb, Creighton C.; McGwin, Gerald; Ponce, Brent A.
Abstract : Background: Excessive radiation to health-care providers has been linked to risks of cancer and cataracts, but its negative effects can be substantially reduced by lead aprons, thyroid shields, and leaded glasses. Hospitals are required to provide education and proper personal protective equipment, yet discrepancies exist between recommendations and compliance. This article presents the results of a survey of U.S. orthopaedic surgery residents concerning attitudes toward radiation exposure and personal protective equipment behavior. Methods: An invitation to participate in a web-based, anonymous survey was distributed to 46 U.S. allopathic orthopaedic surgery residency programs (1, 207 potential resident respondents). The survey was conceptually divided into the following areas: demographic characteristics, training and attitudes concerning occupational hazards, personal protective equipment provision and use, and general safety knowledge. Prevalence ratios (PRs) and 95% confidence intervals (CIs) were calculated for the association between these characteristics and compliance with thyroid shield or lead gown wear. Results: In this study, 518 surveys were received, with 1 survey excluded because of insufficient response, leaving 517 surveys for analysis (42.8% response rate). Ninety-eight percent of residents believed that personal protective equipment should be provided by the hospital or residency program. However, provision of personal protective equipment was not universal, with 33.8% reporting none and 54.2% reporting provision of a gown and thyroid shield. The prevalence of leaded glasses usage was 21%. Poor lead gown compliance and thyroid shield wear were associated with difficulty finding the corresponding equipment: PR, 2.51 (95% CI, 1.75 to 3.62; p < 0.001) for poor lead gown compliance and PR, 2.14 (95% CI, 1.46 to 3.16; p < 0.0001) for poor thyroid shield wear. Not being provided with personal protective equipment was also significantly associated with low compliance with both lead gowns (PR, 1.47 [95% CI, 1.04 to 2.08]; p = 0.03) and thyroid shields (PR, 1.69 [95% CI, 1.18 to 2.41]; p = 0.004). Respondents from the Southeast, West, or Midwest had lower compliance with lead gown usage. Forgetting was the number 1 reason to not wear a lead apron (42%). Conclusions: Radiation exposure is associated with increased risk of serious health problems. Our findings identified that the availability of lead personal protective equipment leads to increased compliance among residents surveyed. In addition to yearly occupational hazard training specific to orthopaedic surgery, greater efforts by residency programs and hospitals are needed to improve access to lead personal protective equipment and compliance for orthopaedic residents.